Interaction of α-Cembrenediol with Human Serum Albumin Based on Spectroscopic and Computational Analyses - Xian-Kun Su; Zhen-Chun Sun; Chang-You Zhao; Hui Yang; Tian-Ming Zhao; Chao Ma; Guo-Fei Zhu (Journal of Spectroscopy)
α-Cembrenediol exhibits a wide range of biological activities, including antibacterial, antitumor, and neuroprotective effects. However, knowledge of the absorption, transport, and release of α-cembrenediol in drug metabolism within the body is currently limited. Therefore, we aimed to gain a comprehensive understanding of the in vivo transport, distribution, and elimination mechanisms of α-cembrenediol and investigate the interaction between α-cembrenediol and HSA. To this end, we utilized various methods including UV absorption spectroscopy, steady-state fluorescence analysis, circular dichroism measurements, molecular docking studies, and molecular dynamics simulations. The results of the UV and fluorescence spectra clearly demonstrated that HSA interacts with α-cembrenediol. Specifically, the fluorescence spectra results showed that at a temperature of 310 K, the fluorescence quenching constant (KSV) and binding constant (Kb) between HSA and α-cembrenediol were determined to be 1.28 × 103 Lmol−1 and 218.27 Lmol−1, respectively. As the temperature was decreased from 310 K to 293 K, both KSV and Kb values increased, indicating the presence of a static quenching mechanism throughout the interaction process. Moreover, the results indicated the presence of a singular, specific binding site for α-cembrenediol on HSA, as evidenced by an approximate count of one binding site at all three temperatures. Additionally, this binding process occurred spontaneously (ΔG < 0), with van der Waals interactions and hydrogen bonding as the primary driving forces (ΔH = −9.40 kJmol−1 and ΔS = −14.50 Jmol−1·K−1). The binding of α-cembrenediol to Sudlow site I of HSA was confirmed through molecular docking, a combination of fluorescence probe substitution, and molecular dynamics simulation experiments. Moreover, the results demonstrated that α-cembrenediol binding led to alterations in the structural conformation of HSA, as confirmed by three-dimensional fluorescence, synchronous fluorescence, and circular dichroism spectra. This study offers crucial insights into the interaction between α-cembrenediol and HSA, contributing to an improved understanding of the compound’s pharmacokinetic properties.